2009
DOI: 10.1007/s10690-009-9099-z
|View full text |Cite
|
Sign up to set email alerts
|

A Remark on a Singular Perturbation Method for Option Pricing Under a Stochastic Volatility Model

Abstract: Approximation accuracy, Option pricing, Partial differential equation, Singular perturbation, Stochastic volatility,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For the case of ρ = 0, the errors of the approximation method are about 2% for all strikes. [17] reported the result that the difference rates of this method for plain vanilla European call OTM options are also relatively high. Our result agrees with that evidence.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of ρ = 0, the errors of the approximation method are about 2% for all strikes. [17] reported the result that the difference rates of this method for plain vanilla European call OTM options are also relatively high. Our result agrees with that evidence.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Fouque et al [4] argues the method for option pricing in detail. The accuracy of the approximation is examined in Yamamoto and Takahashi [17]. In this paper, it is shown that the first order stochastic volatility term is linearly related to the instantaneous correlation between asset value and volatility state.…”
Section: Introductionmentioning
confidence: 98%
“…Especially, Fujii and Takahashi [9] derived an approximation formula for dynamic optimal portfolio in an incomplete market with stochastic volatility, and confirmed its validity through numerical experiment. This paper presents a new analytical approximation method for the FBSDEs based on a Picard-type iteration and an asymptotic expansion (for the asymptotic expansion approach, see Takahashi and Yamada [33] [34] and related previous works [30] [24][31] [35] [29] for example). Also, our method can be regarded as an extension of the representation theorem of BSDEs by Ma and Zhang [23].…”
Section: Introductionmentioning
confidence: 99%
“…For other approximation methods in mathematical finance/financial engineering see for example, Bayer and Laurence [3], Ben Arous and Laurence [4], Gatheral, Hsu, Laurence, Ouyang, and Wang [14], Fouque, Papanicolaou and Sircar [13], Henry-Labordere [25], Kusuoka and Osajima [23], Osajima [34], Siopacha and Teichmann [40], and [10], [11], [12], [18], [55], [60], [61].…”
Section: Introductionmentioning
confidence: 99%